The behaviour of epidemic diseases through the SIR mathematical model: a review of the literature - Casazola Cruz, Oswaldo Daniel (2021)
The article describes the trends in the behavior of epidemic diseases based on the SIR epidemiological model. The objective of this work was to describe the behavior of epidemic diseases based on the SIR epidemiological model from the review of the literature under the methodology of the systematic review based on the PRISMA strategy. The results showed the use of the SIR epidemiological model to describe the behavior of various diseases of an epidemic nature, deepening the disease produced by COVID-19 in recent years in greater frequency. Concluding with the importance of using the SIR model for decision-making as containment measures in the spread of the disease, and the use of an important indicator such as the basic reproduction index to determine the behavior of the disease.